OPTIMALISASI PROMOSI LAYANAN KLINIK DENTAL GALLERY MELALUI MODEL THE FLOWER OF SERVICE - salam, muhammad fery; Lucita, Gina (Politeknik STIA LAN Makassar, 2025)
Digital transformation has reshaped promotional practices in service industries, including dental healthcare services. The Gallery’s Dental Clinic in Makassar faces challenges related to low patient visits and limited digital exposure due to the absence of a structured promotional strategy. This study aims to optimize service promotion through the development of promotional videos based on the Flower of Service model, which integrates core services with supplementary service elements to enhance customer experience. The study employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation involving clinic owners, staff, patients, and non-patients. The findings indicate that promotional videos distributed via Instagram increased digital engagement, strengthened public perceptions of service quality, and attracted new patients. These results demonstrate that integrating the Flower of Service model into video-based promotional content is an effective strategy for improving service visibility and customer interest in dental clinics. The study recommends the consistent development of informative and service-oriented digital content to sustain audience engagement and support long-term service promotion